PERCEPÇÕES DAS CRIANÇAS ACERCA DA GENERIFICAÇÃO DAS BRINCADEIRAS E BRINQUEDOS NA EDUCAÇÃO INFANTIL - Hilton Alves Siqueira Júnior (2025)
The aim of this research is to investigate, based on the perceptions of children aged 4 and 5, the consequences produced by the generification of toys and games present in Early Childhood Education. It takes a qualitative approach, focusing on the analysis of play practices and the use of toys. The theoretical foundation is based on studies on gender (Guacira Lopes Louro - 2014, Richard Miskolci - 2017), childhood (Constantina Xavier Filha - 2012, Juliane Odinino - 2015), school play practices (Lisa Dinella and Erica Weisgram - 2018, Natalia Castellanos - 2013) and power relations (Michel Foucault - 1996, 2008, 2010a, 2010b, 2023). Data was collected using audio recordings, field notes and semi-structured interviews. The research seeks to understand the social markers of difference triggered by the generification of toys and games, to investigate family power relations and their influence on toy choices, and to analyze the consequences of gender binarism in these interactions. It also examines the dynamics of friendship between children throughout the 2024 school year. The results show that power relations, originating in the family context, have a direct impact on children's behavior at school, highlighting the need for inclusive educational practices free of gender stereotypes. The research suggests that both the school and the family play key roles in promoting a gender-equitable education.